2022
DOI: 10.18470/1992-1098-2022-2-102-114
|View full text |Cite
|
Sign up to set email alerts
|

Core areas in the structure of the regional ecological framework of Sevastopol City

Abstract: Aim. To identify land and water areas for inclusion in the regional ecological framework of Sevastopol City and to define the core areas for ensuring the representative character of the nature protection network and the ecological stability of the region.Material and Methods. Based on field surveys, archival and published data, the structure of the ecological framework of Sevastopol was specified as a part of the Crimean ecological network, developed in 2008. A schematic map of the protected areas and ecologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These are the largest in the region SNR "Baydarsky", NP "Protected area "Laspi Rocks", part of the territory of SNR "Cape Aya" and SNR "Laspi". The considered natural cores cover the Yailinsky mountain meadow and steppe landscapes, pine, beech and oak forest zonal landscapes of the southwestern part of the Mountainous Crimea, as well as the sub-Mediterranean complexes of the western part of the lower seaside belt of the southern macroslope of the Crimean Mountains [12][13][14][15][16].…”
Section: Fig 1 the Scheme Of The Main Roads And High-voltage Power Li...mentioning
confidence: 99%
“…These are the largest in the region SNR "Baydarsky", NP "Protected area "Laspi Rocks", part of the territory of SNR "Cape Aya" and SNR "Laspi". The considered natural cores cover the Yailinsky mountain meadow and steppe landscapes, pine, beech and oak forest zonal landscapes of the southwestern part of the Mountainous Crimea, as well as the sub-Mediterranean complexes of the western part of the lower seaside belt of the southern macroslope of the Crimean Mountains [12][13][14][15][16].…”
Section: Fig 1 the Scheme Of The Main Roads And High-voltage Power Li...mentioning
confidence: 99%
“…The research angle of ecological projects have shown a diversified trend, Bronwen et al’ s research on restoration projects on the California Central Coast showed that the restoration activity is consistent with ecological need, concentrated in human settlements and near restoration organizations 12 ; Milchakova et al’s research showed that the implementation of the ecological framework project will help to reduce the risk of losing the biological and landscape diversity of Sevastopol City 13 ; Roy et al expounded design, governance, and outcomes of the Flagstaff Watershed Protection Project 14 . In China, the research related to ecological projects mainly focuses on GGP.…”
Section: Introductionmentioning
confidence: 99%